Efficient routing for IP subnet VLAN over Ethernet - Kok, Chan Wai; Salim Beg, M. (John Wiley & Sons, 2002)
Existing IP routing algorithms have been developed mainly for non-VLAN networks. For these routing algorithms to work, an end station must be attached to its associated network. The introduction of VLAN hits, however, allowed the physical location of the end station to be changed from time to time. Therefore, some extra mechanism is required to support routing in VLAN environment. Existing approaches have some drawbacks in terms of inefficiency in traffic forwarding and switch software complexity. In this paper, a simple and efficient method for routing over IP subnet VLAN in Ethernet is proposed. This method has been implemented in hardware and found to work correctly. Various measurements and analyses have been performed to verify the efficiency of this protocol. Copyright (C) 2002 John Wiley Sons, Ltd.